Analisis Perbuatan Melawan Hukum Dalam Pembagian Waris Adat Batak Studi Putusan No. 537 K/Pdt/2017 (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
Inheritance law is a regulation that regulates the legal position of the assets of a person who has died, which will later change hands to another person who has the right to receive the assets. Inheritance law in Indonesia applies 3 (three) types of inheritance law, namely customary inheritance law, Islamic inheritance law, and western inheritance law. In carrying out this inheritance system, in its implementation there are still several errors and unlawful acts committed by the parties, such as in decision NO. 537 K/Pdt/2017. In this decision, it was discovered that there were unlawful acts in the distribution of inheritance in the Batak tribe. The Batak tribe adheres to a patrilineal family system, which means that the bloodline is drawn from male parents or fathers, so that the position of fathers or men in traditional society can be said to be higher than women.